Tendon overload results in alterations in cell shape and increased markers of inflammation and matrix degradation. Issue 4 (30th December 2014) - Thorpe, C. T.; Chaudhry, S.; Lei, I. I.; Varone, A.; Riley, G. P.; Birch, H. L.; Clegg, P. D.; Screen, H. R. C.
<x xml:space="preserve">Abstract</x> Tendon injury is thought to involve both damage accumulation within the matrix and an accompanying cell response. While several studies have characterized cell and matrix response in chronically injured tendons, few have assessed the initial response of tendon to overload‐induced damage. In this study, we assessed cell response to cyclic loading. Fascicle bundles from the equine superficial digital flexor tendon were exposed to cyclic loading in vitro, designed to mimic a bout of high‐intensity exercise. Changes in cell morphology and protein‐level alterations in markers of matrix inflammation and degradation were investigated. Loading resulted in matrix damage, which was accompanied by cells becoming rounder. The inflammatory markers cyclooxygenase‐2 and interleukin‐6 were increased in loaded samples, as were matrix metalloproteinase‐13 and the collagen degradation marker C1, 2C. These results indicate upregulation of inflammatory and degradative pathways in response to overload‐induced in vitro, which may be initiated by alterations in cell strain environment because of localized matrix damage. This provides important information regarding the initiation of tendinopathy, suggesting that inflammation may play an important role in the initial cell response to tendon damage. Full understanding of the early tenocyte response to matrix damage is critical in order to develop effective treatments for tendinopathy.